OPTIMALISASI PENGOLAHAN BAHAN PUSTAKA DI KANTOR PERPUSTAKAAN DAN ARSIP DAERAH KABUPATEN KARIMUN - Said Nuwrun Thasimmim (Prodi Ilmu Administrasi Negara, 2019)
The library materials management is one of the main activities in a series of library process. This activities allow the library collections to be organized in a systematic, effective and efficient manner. The performance of processing library materials greatly influences the success of the library in carrying out its duties and functions. This study aims to examine the optimization of processing library materials in the Regional Library and Archives Office of Karimun Regency. The approach used in this study is a qualitative approach. The population in this study were all staff at the Regional Library Office and the Archives of Karimun Regency totaling 48 people. With a sample of 10 people, namely 5 civil servants and 5 honorary people. As the result of the study concluded that here are several things that can be done by universities in order to change the community's stigma about the existence of universities. First, with more professional library management. Second, the development of a library with adequate facilities. The building or library room is quite good, in the sense that it is adequately visited by visitors. This is inseparable from the maintenance of space and buildings by librarian officers as a place to store collections of library materials, librarian workplaces, and reading rooms for library users. library equipment owned by the library and archives of the District of Karimun are library materials, research cabinets for goods, tables, chairs, collection shelves, library materials, magazines, newspapers, book stroller, and wall boards.